Current Use and Complementary Value of Combining in Vivo Imaging Modalities to Understand the Renoprotective Effects of Sodium-Glucose Cotransporter-2 Inhibitors at a Tissue Level - van der Hoek, Sjoukje; Stevens, Jasper (Frontiers in Pharmacology, 2022)
Sodium-glucose cotransporter-2 inhibitors (SGLT2i) were initially developed to treat diabetes and have been shown to improve renal and cardiovascular outcomes in patients with- but also without diabetes. The mechanisms underlying these beneficial effects are incompletely understood, as is the response variability between- and within patients. Imaging modalities allow in vivo quantitative assessment of physiological, pathophysiological, and pharmacological processes at kidney tissue level and are therefore increasingly being used in nephrology. They provide unique insights into the renoprotective effects of SGLT2i and the variability in response and may thus contribute to improved treatment of the individual patient. In this mini-review, we highlight current work and opportunities of renal imaging modalities to assess renal oxygenation and hypoxia, fibrosis as well as interaction between SGLT2i and their transporters. Although every modality allows quantitative assessment of particular parameters of interest, we conclude that in particular the complementary value of combining imaging modalities in a single clinical trial aids in an integrated understanding of the pharmacology of SGLT2i and their response variability.